Epizootic situation on toxoplasmosis in the Crimea - G. A. Lukyanova; M. V. Makarova; M. V. Galat; N. A. Makarevich; I. A. Gurenko (Аграрная наука Евро-Северо-Востока, 2017)
Novaday problems of definition of toxoplasmosis on Crimea peninsula area are presented in the article. Monitoring studies of cats and sheeps are spent on existing of T. gondii agent in different sites of Crimea peninsula. Significant defeat of cats by T. gondii agent is established (21.8% of total studied cats). Homeless cats of cities’ populations had higher persent of toxoplasma invalion than animals of rural areas and consists 14.55%. Sheeps also had toxoplasmosis (average degree ofinvasion was 14.7%). Thus female animals had highest infection rate: invasion persent was 16.3%. Male animals had lower degree of toxoplasma invasion - 10.5% of sheeps had antibodies to Toxoplasma gondii in their blood serum. Sixty persent of invasious animals belongs to oldest groups (sheeps of 2-4 years old), 40% of animals earlier than 1 year were infected. Investigated animsl species are potential sources of infectious for human that is proved by statistical analysis. According to the data of department of statistics of medicinal parasitology of sanitary-epizootological station of Crimea Republic it is detected significant level of distribution of T. gondii invasion among peninsula’s population. Average invasioness of peoples by toxoplasma in Crimea Republic in 2015 was 12.02%. Peoples of 7to 20 years old had 4.23% of invasion rate, older peoples (50-60 years old) - 31.04%. In group of pregnanted women antibodies to toxoplasma agent is revealed in 37.03% of human .